2014
DOI: 10.1590/1981-6723.1214
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento reológico e efeito da temperatura da polpa de pequi em diferentes concentrações

Abstract: ResumoApesar do elevado potencial econômico da polpa pequi ainda são escassos os trabalhos sobre suas propriedades físicas utilizadas em projetos e processos industriais. Diante disso, objetivou-se estudar o comportamento reológico da polpa de pequi com diferentes teores de sólidos solúveis totais (6, 8, 10 e 12 °Brix) e em diferentes temperaturas (25, 30, 35, 40, 45 e 50 °C). As medidas experimentais foram realizadas em viscosímetro Brookfield e os modelos reológicos de Ostwald-de-Waelle, Herschel-Bulkley e M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
2
2
0
4
Order By: Relevance
“…Similar results have been reported by Sousa et al (2014), Quek et al (2013) and Silva et al (2005), who observed that activation energy increased as soluble solids of pequi pulp, soursop juice and acerola juice, respectively, decreased. Activation energy also gradually increased when Totapuri mango solids concentration decreased, as reported by Dak et al (2006).…”
Section: Santos P H Et Alsupporting
confidence: 90%
“…Similar results have been reported by Sousa et al (2014), Quek et al (2013) and Silva et al (2005), who observed that activation energy increased as soluble solids of pequi pulp, soursop juice and acerola juice, respectively, decreased. Activation energy also gradually increased when Totapuri mango solids concentration decreased, as reported by Dak et al (2006).…”
Section: Santos P H Et Alsupporting
confidence: 90%
“…They are also of fundamental importance in energy saving, which is becoming increasingly important. This can be seen in the studies of Sousa et al (2014).…”
Section: Resultsmentioning
confidence: 71%
“…Se encontró que el índice de flujo no sigue una relación lineal con el inverso de la temperatura descrito a través del modelo de Arrhenius. Resultados similares han sido descritos en jugo de mango, pulpa de piqui (C. coriaceum) y suspensiones alimentarias fluidas y semisólidas (Dark, Verma, & Sharma, 2006;Rao, 2006;Souza et al, 2014). No obstante, un modelo lineal describió satisfactoriamente el comportamiento entre el índice de flujo y la temperatura, con valores del coeficiente de determinación (R 2 ) entre 0,74 y 0,94 y bajos valores del CME (tabla 2, figura 2B).…”
Section: Efecto De Temperatura Y Concentración Sobre Los Parámetros Runclassified